Paracentral acute middle maculopathy with cerebral infarction caused by carotid dissection: a case report - Tang, Huiqiong; Liu, Lu; Cao, Le; Liu, Junfeng; Wu, Bo (Frontiers in Neurology, 2025)
IntroductionParacentral acute middle maculopathy (PAMM) is related to retinal capillary ischemia, occurring independently or secondary to systemic diseases. We report an unusual case of PAMM with cerebral infarction caused by carotid dissection without systemic risk factors.Case descriptionA 55-year-old man presented with acute painless left visual loss and partial sensory aphasia, followed by right-sided weakness. Best-corrected visual acuity (BCVA) was 0.04 in the left eye. Optical coherence tomography (OCT) showed hyperreflective lesions at the OPL-INL junction; enface imaging revealed fern-like hyperreflective lesions in the inner nuclear layer (INL). OCT angiography (OCTA) demonstrated diffuse macular hypoperfusion. Brain MRI showed left basal ganglia infarction, and angiography confirmed left internal carotid artery (ICA) dissection and near occlusion. After carotid stenting and dual-antiplatelet therapy, BCVA improved to 0.8 at 3 months with OCTA-confirmed retinal reperfusion.ConclusionThis is a report that links PAMM and cerebral infarction to carotid dissection, suggesting that PAMM should prompt urgent stroke and carotid workup in appropriate clinical context.